Environmental threats to pollinator health and fitness - Harrison, Jon F. (Advances in insect physiology, 2023)
Environmental Threats to Pollinator Health and Fitness, Volume 64 in the Advances in Insect Physiology series, highlights new advances in the field, with this new volume presenting interesting chapters on a variety of topics, including The threat of higher temperatures to pollinating insects, The challenge of balancing fungicide use and pollinator health, Insecticide effects on pollinating insects, Effects of invasive pathogens and parasites on pollinating insects, Heavy metal pollutants: the hidden pervasive threat to honey bees and other pollinators, Honey bee nutritional ecology: from physiology to landscapes, and more.